Musculoskeletal asymmetry in young soccer players: Differences between the dominant and nondominant leg - Taketomi, S.; Kawaguchi, K.; Mizutani, Y.; Yamagami, R.; Sameshima, S.; Takei, S; Kage, T.; Kono, K.; Inui, H.; Fujiwara, S.; Tanaka, S.; Ogata, T. (International Journal of Human Movement and Sports Sciences, 2022)
The purpose of this investigation was to clarify the differences in the musculoskeletal profiles between the dominant leg (DL) and nondominant leg (NDL) of Japanese soccer players. This study included 227 young elite soccer players (121 males and 106 females with mean ages of 19.0 and 17.5 years, respectively). Anthropometric measurements were obtained. In addition, joint range of motion measurements was performed for internal rotation of the hip, ankle dorsiflexion, and knee extension. Muscle flexibility tests were performed on the iliopsoas, quadriceps femoris, hamstring, gastrocnemius, and soleus muscles. Moreover, isometric knee extension, flexion strength, and isometric hip abduction strength were measured. Single-leg balance tests were also performed. As a result, in male soccer players, DL's knee flexor strength and hip abductor strength were significantly stronger than in the NDL. In female soccer players, knee extension and knee flexion strength of the DL were significantly stronger than the NDL. In male soccer players, the hamstring-quadriceps ratio of the DL was significantly greater than NDL. DL demonstrated a significantly lesser center of pressure excursion in the single-leg balance test in male and female soccer players. In both male and female soccer players, the quadriceps muscle of DL was significantly more flexible than those of the NDL. There was no difference in the internal rotation angle of the hip joint between the DL and NDL in male soccer players. In contrast, the internal rotation angle of the DL was significantly (1.6°) greater than NDL in female soccer players. For some anthropometric measurements, muscle flexibility tests and joint range of motion measurements, the difference between the DL and NDL was significant but not large enough to be clinically relevant. In conclusion, the present study showed musculoskeletal asymmetry between the DL and NDL in young male and female soccer players.